Assessing plume impacts caused by polymetallic nodule mining vehicles. (May 2022) - Weaver, P.P.E.; Aguzzi, J.; Boschen-Rose, R.E.; Colaço, A.; de Stigter, H.; Gollner, S.; Haeckel, M.; Hauton, C.; Helmons, R.; Jones, D.O.B.; Lily, H.; Mestre, N.C.; et al.
Abstract: Deep-sea mining may be just a few years away and yet society is struggling to assess the positive aspects, such as increasing the supply of metals for battery production to fuel the green revolution, versus the potentially large environmental impacts. Mining of polymetallic (manganese) nodules from the deep ocean is likely to be the first mineral resource targeted and will involve direct impacts to hundreds of km 2 of seabed per mine per year. However, the mining activity will also cause the generation of large sediment plumes that will spread away from the mine site and have both immediate and long-term effects over much wider areas. We discuss what the impacts of plumes generated near the seabed by mining vehicles may be and how they might be measured in such challenging environments. Several different mining vehicles are under development around the world and depending on their design some may create larger plumes than others. We discuss how these vehicles could be compared so that better engineering designs could be selected and to encourage innovation in dealing with plume generation and spread. These considerations will aid the International Seabed Authority (ISA) that has the task of regulating mining activities in much of the deep sea in its commitment to promote the Best Available Technology (BAT) and Best Environmental Practice (BEP).